The Customer Engagement Approaches of Influential Entrepreneurship : Based on business related Customer Engagement approaches emerged on Weibo - Zhou, Yang (fi=Turun yliopisto|en=University of Turku|, 2018)
This study focuses on an emerging field of Influential Entrepreneurship to research the adoption of Customer Engagement Approaches as effective business strategies in China context. The aim is to establish an interactive framework combining theoretical findings and empirical evidence to illustrate the Customer Engagement Approaches enacted by Influential Entrepreneurs. The primary data is collected from expert Interviewees, and raw data is later interpreted, categorized, and grouped with thematic networks to display the logic and relationship of different terms. An interactive framework of Customer Engagement Approaches by Influential Entrepreneurs is put forward, and the framework sheds lights both on theoretical contributions and practical implications. Suggestions for future researches are discussed in the end to provide scholars with academic indications. The study confirms that Customer Engagement Approaches are vigorously employed by Influential Entrepreneurs as efficient business strategies. Influential position themselves as knowledgeable, informative, and communicative figures with commonality and attainability so as to establish profit-oriented intimate relationship via Customer Engagement Approaches. Customer Engagement approaches vary from case to case, and approaches include commoditization of contents production, management of persona, display of friendliness, presentation of perceived authenticity and intimacy, mostly through mixed social media related activities with a supplement in offline events. In this case, Influential Entrepreneurs exploit customers¡¯ desire from multiple perspectives and trigger contagion effects, leading to mutually amplified effects in economic returns, popularity, business opportunities, and communication effects. Specifically, Influential Entrepreneurs deems tangible value triggered interaction as temporary, while they consider relationship-oriented interaction as profoundly effective. Multi-channelling effects of social media platforms are particularly added to the scaling up of customer base. Influential endorsements are charged with emotional premium, which is similar with corporate charged brand premium.